2015
DOI: 10.1089/neu.2015.3873
|View full text |Cite
|
Sign up to set email alerts
|

Acute Temporal Profiles of Serum Levels of UCH-L1 and GFAP and Relationships to Neuronal and Astroglial Pathology following Traumatic Brain Injury in Rats

Abstract: A number of potential traumatic brain injury (TBI) biomarkers have been proposed and evaluated in the laboratory and clinic. This study investigated the temporal profile of circulating biomarkers of astrocytic and neuronal injury over the first 24 h and relevant histopathological changes after experimental moderate TBI. Twenty male rats were randomly assigned to either moderate parasagittal fluid percussion or sham injury. Blood serum samples were collected 2 d prior to TBI (baseline) and at 3, 6, and 24 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 38 publications
3
43
0
2
Order By: Relevance
“…However, this was not found in intracranial hemorrhage (43). It has been also revealed that increased serum levels of UCH-L1 reflect neuropathology, such as subcortical white matter lesion and increased level of UCH-L1 level in the CSF (44,45). Thus, UCH-L1 was suggested as an indicator of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not found in intracranial hemorrhage (43). It has been also revealed that increased serum levels of UCH-L1 reflect neuropathology, such as subcortical white matter lesion and increased level of UCH-L1 level in the CSF (44,45). Thus, UCH-L1 was suggested as an indicator of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…UCH-L1 is expressed in neurons and is responsible for either the addition or removal of ubiquitin proteins damaged by oxidation (Mondello et al, 2011). Both serum GFAP and UCH-L1 are increased less than1 hour after TBI and are used as specific markers for the magnitude of brain injury (Huang et al, 2015;Papa et al, 2016;Wang, Yang, Sarkis, Torres, & Raghavan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…21,26,56,107 Using immunoblotting, we found elevations in total GFAP and GFAP-DPs in serum at 3 days after CCI, which corresponded to CNS levels. Huang and colleagues did not find elevated GFAP in serum at 24 hours after TBI; however, they used a different age (adults), injury mechanism (fluid percussion), and method of detection (enzyme-linked immunosorbent assay [ELISA]), 30 differences that emphasize the need for age and assay specificity. Nonetheless, GFAP and GFAP-DPs and αII-SDPs are emerging as sensitive serum biomarkers.…”
Section: Discussionmentioning
confidence: 99%